2006
DOI: 10.1128/iai.74.1.794-797.2006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Lethal Toxin-Neutralizing Antibody Titers and Protection from Intranasal Challenge with Bacillus anthracis Ames Strain Spores in Mice after Transcutaneous Immunization with Recombinant Anthrax Protective Antigen

Abstract: Transcutaneous immunization of mice with recombinant protective antigen (rPA) of Bacillus anthracis resulted in significantly higher lethal toxin-neutralizing antibody titers than did intramuscular injection of alum-adsorbed rPA. Immunized mice were partially protected against intranasal challenge with 235,000 (10 50% lethal doses) Ames strain B. anthracis spores. A highly significant correlation was observed between toxin-neutralizing antibody titer and survival after challenge. Future experiments with rabbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 14 publications
2
50
0
Order By: Relevance
“…The amount of each antigen(s) was 1.25 μg displayed on 4 × 10 10 hoc -soc -phage particles in phosphate buffered saline without any adjuvant. The mice were bled every 2 weeks and sera from individual mice were assayed for the presence of PA, LF, and EF-specific IgG using an enzyme-linked immunosorbent assay (ELISA) [31]. Briefly, 96-well flat-bottomed Nunc Maxisorp plates (VWR, Bridgeport, NJ) coated with 0.1 μg/well of purified recombinant PA, LF or EF were blocked overnight with 0.5% gelatin in PBS, washed and incubated overnight with the test serum followed by HRP-labeled, affinity purified goat anti-mouse IgG (The Binding Site, San Diego, CA) and ABTS substrate (KPL, Gaithersburg, MD).…”
Section: Immunogenicity Studiesmentioning
confidence: 99%
“…The amount of each antigen(s) was 1.25 μg displayed on 4 × 10 10 hoc -soc -phage particles in phosphate buffered saline without any adjuvant. The mice were bled every 2 weeks and sera from individual mice were assayed for the presence of PA, LF, and EF-specific IgG using an enzyme-linked immunosorbent assay (ELISA) [31]. Briefly, 96-well flat-bottomed Nunc Maxisorp plates (VWR, Bridgeport, NJ) coated with 0.1 μg/well of purified recombinant PA, LF or EF were blocked overnight with 0.5% gelatin in PBS, washed and incubated overnight with the test serum followed by HRP-labeled, affinity purified goat anti-mouse IgG (The Binding Site, San Diego, CA) and ABTS substrate (KPL, Gaithersburg, MD).…”
Section: Immunogenicity Studiesmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of PA in vaccines to protect against anthrax intoxication or infection [10][11][12][13]. The importance of anti-PA serum also has been shown in the identification of in vitro correlates of immunity [14][15][16][17] and in passive antibody studies [18][19][20]. This report evaluates the role of the aluminum hydroxide gel adjuvant and the excepient formaldehyde in the formulation of rPA vaccines in the rabbit model using in vitro surrogate markers (the quantitative anti-rPA IgG ELISA and toxin neutralizing antibody (TNA) assay) and efficacy studies.…”
Section: Subject Termsmentioning
confidence: 99%
“…We did not observe a decrease in the TNA assay ED 50 titers in the rabbit animal model at the highest concentration of aluminum tested (500 g). Both the anti-PA ELISA titer and toxin neutralizing antibody titers have been identified as serological correlates of immunity in rabbits and guinea pigs [13][14][15][16][17]25] and are thus important measurements in developing effective vaccine strategies. Various formulations have been tested in preparing anthrax vaccines based upon rPA for its ability to elicit optimal immunological responses.…”
Section: Effect Of Formaldehyde On Serological Response and Protectionmentioning
confidence: 99%
“…In this feasibility study, we did not evaluate various doses or immunization regimens; however, previous work has found induction of immune responses following transcutaneous immunization with as little as 1 g of antigen and 10 g of immunoadjuvant (13,29). Previous work has also shown that, when antigen is used alone, three or four transcutaneous applications of antigen are usually required to induce immune responses to topically applied antigens (10,12,14).…”
Section: Vol 74 2006mentioning
confidence: 99%